Comparative study of learning analytics techniques to predict student academic performance in higher education - Acosta-Gonzaga, Elizabeth (Universidad Autónoma de Tamaulipas, 2020)
The issue of school dropout involves factors such as students’ engagement that can predict his or her success in school. It has been shown that student engagement has three components: behavioral, emotional and cognitive. Motivation and engagement are strongly related since the former is a precursor of engagement. The aim of this study was to compare the efficiency of linear regression against two data mining techniques to predict the students’ academic performance in higher education. A descriptive cross-sectional study was carried out with 222 students from a public higher education institution in Mexico city. An analysis of hierarchical linear regression (LR) and learning analytics techniques such as neural networks (NN) and support vector machine (SVM) was conducted. To assess the accuracy of the learning analytics techniques, an analysis of variance (ANOVA) was carried out. The techniques were compared using cross validation. The results showed that behavioral engagement and self-efficacy had positive effects on student achievements, while passivity showed a negative effect. Likewise, the LR and SVM techniques had the same performance on predicting students’ achievements. The LR has the advantage of producing a simple and easy model. On the contrary, the SVM technique generates a more complex model. Although, if the model were aimed to forecast the performance, the SVM technique would be the most appropriate, since it does not require to verify any statistical assumption.